Do We Know Enough About Radiation Exposure and Its Side Effects in Invasive Cardiological Procedures? - Aydin, Saadet; Kocak, Ajar; Demir, Yusuf; Senoz, Oktay; Isik, Omer; Ekici, Berkay (Sage Publications Inc, 2025)
In the present study, radiation exposure rates of patients undergoing various invasive cardiological procedures, associated skin side effects, and the impact of radiation protection training for operators were evaluated. A total of 523 patients were included, of whom 206 (39.4%) were female and 317 (60.6%) were male. Radiation exposure levels and skin side effects were recorded. A positive correlation was observed between fluoroscopy dose (mGy) and patients' body mass index (BMI) (P < .001). Additionally, male patients were exposed to significantly higher radiation doses than females (P < .003). Within 1 month post-procedure, skin-related side effects such as itching (6.3%) and dryness (5.4%) were reported. Patients undergoing more complex procedures, including percutaneous transluminal angioplasty (PTA), percutaneous coronary intervention (PCI), and coronary artery bypass grafting (CABG) imaging, had higher radiation doses and longer exposure times compared with other procedures. Following a seminar on radiation protection, a significant reduction in procedural radiation exposure was noted, indicating increased operator awareness. This study highlights the importance of procedural complexity, patient characteristics, and operator training in managing radiation risks during cardiological interventions.
Keywords: invasive cardiology; skin lesions; radiation exposure